Aliens, Humans, Animals, & Luck: Animal Treatment & Human Morality - Firestone, Randall S. (Scientific Research, 2016)
This paper proposes two thought experiments to demonstrate that our current treatment of animals is immoral. The first thought experiment involves aliens coming to earth and doing to us what we do to animals—eating us, confining us in farms and zoos, doing experiments on us, etc. Drawing on the latest scientific research on the abilities of animals, this thought experiment seeks to show that there are more relevant similarities between human beings and animals than most people realize, and that the differences between us and many other animals are not morally relevant. Moreover, this thought experiment attempts to appeal primarily to our sense of justice by tapping into our emotions for ourselves rather than to the usual approach which appeals to our emotions for animals. The second thought experiment is similar to the first, but more centrally emphasizes the idea of luck. It will, in part, take an approach recommended by Donald VanDeVeer to employ Rawl’s veil of ignorance to mask not only our natural and social starting places, but also our species—whether we are human or of another species. However, one serious objection made to VanDeVeer’s approach will be circumvented, namely, that it is difficult to imagine ourselves as an animal. Rather, we will imagine that evolution has made it so we are not the smartest and most powerful species on earth. This thought experiment invites us to ask ourselves that if there were only two species to consider and we were the less advanced of the two, would we still not expect to be treated with dignity and respect? Both analogies ultimately challenge us to ask the following question: What principles of justice would we choose to govern the interactions between species if we were not the most intelligent and powerful species on earth?
Keywords: Animal Rights; Animal Welfare; Animals; Alien Analogy; Veil of Ignorance; Species; Thought Experiment